Acute renal failure due to Brucella melitensis - Ozgur Dagli; Mehmet Dokur; Gulcihan Guzeldag; Yelda Ozmen (Journal of Infection in Developing Countries)
We present the case of a 42-year-old male patient who applied to the emergency department of our hospital with clinical nephritis, orchitis, acute renal failure without endocarditis, and a low-grade fever. Brucella agglutinin titers were 1:160, Rose Bengal test was positive and Brucella melitensis was isolated from urine and blood cultures.. A combination of oral rifampin (600 mg/day) and doxycycline (200 mg/day) was administered along with supportive treatment leading to resolution of his clinical status by eight weeks. This was a rare complication of severe renal involvement due to brucellosis which resolved with antibiotic treatment.